Pneumatosis Cystoids Intestinalis as Cause of Unnecessary Surgery: Clinical Case - Guerrero-Ortega, Noely Xochitl Leonor; Flores-López, Alejandro Alberto; Sevilla-Flores, José Guadalupe; Figueroa-Araujo, Demián; Guerrero-Ortega, Lena; Romero-Macías, Arturo; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Background: The causes of PCI vary; 85% are secondary to other conditions such as abdominal pain from trauma, intestinal obstruction, inflammatory bowel disease, malignancies, chemo radiotherapy, chronic lung diseases, and connective tissue diseases. Diagnosis is challenging due to asymptomatic or atypical symptoms. Endoscopic ultrasonography (EUS) and endoscopic fine-needle aspiration are helpful for the diagnosis and treatment of PCI. Clinical Case: A 54-year-old female patient income for abdominal pain. Background: rheumatoid arthritis treated with prednisone for five years, surgical: cesarean section 11 years ago, Hartmann procedure for complicated diverticular disease in November 2020, intestinal transit restoration surgery in April 2021, referred allergy to aminoglycosides. We performed an exploratory laparotomy, which obtained the following findings: "scarce intra-abdominal free air, ten mL of inflammatory reaction fluid in the cavity, diverticula among 2-3 cm in diameter. Cystic formations in the mesenteric border of approximately 5 mm in diameter at the level of the jejunum and proximal ileum with cystic pneumatosis in the mesentery of the jejunum and proximal ileum 150 cm to 170 cm from the angle of Treitz and 80 cm from the ileocecal valve. Discussion: PCI is associated with a wide variety of underlying conditions such as chemotherapy; underlying malignancy, and graft-versus-host disease (GVHD), long-term steroid treatment has also been reported to be associated with PCI. Gastrointestinal GVHD occurs infrequently in patients suffering from chronic GVHD after successful treatment of bone marrow transplantation (BMT) or stem cell transplantation which can lead to mucosal damage and increased apoptosis between mucosal cells and cells inside the intestinal wall. These alterations can result in diarrhea, abdominal pain, malnutrition, and pseudo-obstruction, which can increase extraintestinal pressure and cause PCI.